Health professionals’ involvement in volunteering their professional skills: a scoping review - Strkljevic, Ima; Tiedemann, Anne; Souza de Oliveira, Juliana; Haynes, Abby; Sherrington, Cathie (Frontiers in Medicine, 2024)
Background: Volunteering positively affects overall health of both volunteers and recipients through social interaction, support and physical activity. Health professionals' volunteering has considerable potential to improve health outcomes in communities.Objectives: This study aimed to summarize published scientific literature regarding volunteering by health professionals.Method: Medine, Embase, Scopus, PsycINFO and CINAHLSix databasesdatabases were searched to identify eligible studies published between 2010 and 2023. Data on study methods and findings were extracted and synthesized.Results: Of the 144 eligible studies, 80 (56%) used quantitative methods, 46 (32%) used qualitative, 18 (12%) used mixed methods and 8 (6%) were interventional. Doctors (74 studies, 51%) and nurses (n=40, 28%) were the professions with most reports of volunteering. Half the studies were from USA (n=77, 53%), followed by UK (n=19, 13%), Canada (n=12, 8%), and Australia/New Zealand (n=11, 8%). International volunteering in low-to-middle-income countries was the most commonly reported locationin 64 studies (n=64, 44%). Providing service and training were the dominant types of activities (n=90, 62.5%), with health promotion reported in only 4 studies (3%). Studies reported positive impacts from volunteering, both professionally and personally. Time and family commitments were the main barriers. Enablers, barriers and impact were summarized in a socio-ecological map.Health professionals volunteer in diverse activities and report multifaceted benefits. Studies of volunteering interventions could enable new, sustainable approaches to health promotion.